Comparison of massage and prone position on heart rate and blood oxygen saturation level in preterm neonates hospitalized in neonatal intensive care units - Hanan Mostafa El-sayd; Ghada Mohamed El-Mashad; Mohamed Zakaria Elsaied Mohamed; Zeinab Sabri Abouzouna (SpringerOpen, 2023)
Abstract Background Many years ago, it was proposed that prone positioning and infant massage would benefit preterm and babies with low birth weight. Aim of the work Evaluating the effectiveness of massage therapy and the neonatal prone position on the heart rate (HR) and blood oxygen saturation level (SPO2) of premature neonates in neonatal intensive care units. Subject and methods Our study was conducted as a single-center, randomized controlled clinical trial at the NICUs of Menoufia University Hospital. After enrollment, the (240) cases were divided into group A: (80) infants with prone position, group B: (80) infants with massage therapy (as intervention groups), group C: (80) infants as a control group (without intervention). Results Regarding group A, there was a significant difference between the first and last days of intervention regarding HR and SPO2 at 15, 30, 45, and 60 min. Regarding group B, there was a significant difference between the first and last days of intervention regarding HR and SPO2 at 15, 30, 45, and 60 min. Regarding group C, there was no significant difference between the First and last days of intervention regarding HR at 15, 30, 45, and 60 min. Conclusion Prone position and infant's massage equally reduce Heart Rate and increase preterm babies' blood oxygen saturation level neonates admitted in NICU.